2022
DOI: 10.1192/bjo.2022.542
|View full text |Cite
|
Sign up to set email alerts
|

Exploring patients' experience of peer-supported open dialogue and standard care following a mental health crisis: qualitative 3-month follow-up study

Abstract: Background Experience of crisis care may vary across different care models. Aims To explore the experience of care in standard care and ‘open dialogue’ (a peer-supported community service focused on open dialogue and involving social networks for adults with a recent mental health crisis) 3 months after a crisis. Method We conducted semi-structured interviews with 11 participants (6 received open dialogue; 5 received treatment as usual (TAU)) in a feasibility study of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…These have explored the impact of the Open Dialogue approach on mental healthcare practitioners, clients and networks. For example, studies of patient experience and outcomes found that Open Dialogue helped patients to feel heard and supported (Jacobsen et al, 2018;Bergström et al, 2019;Sunthararajah et al, 2022) and improved social functioning and quality of life by standard measures (Kinane et al, 2022). Studies of treatment sessions showed that dialogue which allowed clients to dominate and involved symbolic (rather than pragmatic) language was associated with good outcomes from psychotic crisis (Seikkula, 2007).…”
Section: Anthropology and Open Dialoguementioning
confidence: 99%
“…These have explored the impact of the Open Dialogue approach on mental healthcare practitioners, clients and networks. For example, studies of patient experience and outcomes found that Open Dialogue helped patients to feel heard and supported (Jacobsen et al, 2018;Bergström et al, 2019;Sunthararajah et al, 2022) and improved social functioning and quality of life by standard measures (Kinane et al, 2022). Studies of treatment sessions showed that dialogue which allowed clients to dominate and involved symbolic (rather than pragmatic) language was associated with good outcomes from psychotic crisis (Seikkula, 2007).…”
Section: Anthropology and Open Dialoguementioning
confidence: 99%
“…The model prioritizes providing permanent housing to people experiencing homelessness in an attempt to integrate care and recovery initiatives [91]. Other programs that focus on more personal and social aspects of care and recovery are Peer-Supported Open Dialogue [92,93], Wellness Recovery and Action Plan (WRAP) [94], Individual Placing and Support (IPS) focusing on rehabilitation in work and education [95], and variants of assertive community treatment (ACT) such as resource-group ACT and flexible-ACT [96].…”
Section: Examples Of Public Mental Health Initiatives In Industrializ...mentioning
confidence: 99%